2012
DOI: 10.1007/s10930-012-9421-x
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Analyses Identified Three Amino Acid Residues Critical to the Catalysis of Two Aphid Farnesyl Diphosphate Synthase

Abstract: Farnesyl diphosphate synthase (FPPS) plays an essential role in the isoprenoid biosynthetic pathway of microbes, plants and animals. In the present study, we first cloned two FPPSs from the bird cherry-oat aphid (RpFPPS1 and RpFPPS2), and activity assay by gas chromatography-mass spectrometry showed that both RpFPPS1 and RpFPPS2 were active in vitro. They were then subjected to homology modeling and molecular docking. Molecular interaction analysis indicated that three amino acid residues (R120, R121 and K266)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Interestingly, only one FPPS gene existed in the cotton aphid Aphis gossypii , whereas most other aphid species (eg M . persicae and Rhopalosiphum padi ) had two FPPS genes (Zhang and Li, ; Ma et al, ; Sun and Li, ). The GGPP synthase (GGPPS) was functionally analysed in vitro in A .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, only one FPPS gene existed in the cotton aphid Aphis gossypii , whereas most other aphid species (eg M . persicae and Rhopalosiphum padi ) had two FPPS genes (Zhang and Li, ; Ma et al, ; Sun and Li, ). The GGPP synthase (GGPPS) was functionally analysed in vitro in A .…”
Section: Introductionmentioning
confidence: 99%
“…The FPP synthases (FPPSs) displayed dual GPP synthase (GPPS)/FPPS activity in the green peach aphid Myzus persicae (Lewis et al, 2008;Vandermoten et al, 2008;Zhang and Li, 2012). Interestingly, only one FPPS gene existed in the cotton aphid Aphis gossypii, whereas most other aphid species (eg M. persicae and Rhopalosiphum padi) had two FPPS genes (Zhang and Li, 2008;Ma et al, 2010;Sun and Li, 2012). The GGPP synthase (GGPPS) First published online 12 September 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, we cloned two full-length cDNAs ( RpFPPS1 and RpFPPS2 ) coding for FPPS in the bird cherry-oat aphid Rhopalosiphum padi (Sun & Li, 2012). Recombinant expression and in vitro enzymatic activity assay showed that both FPPSs could utilize isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) to produce FPP.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, FPPS genes have been studied in aphids partially due to their association with the biosynthesis of EβF (Vandermoten et al, ). In our group, we have isolated and characterized several FPPSs from different aphid species, such as the green peach aphid Myzus persicae (Y. L. Zhang & Li, , 2012), the cotton aphid Aphis gossypii (Ma, Sun, Zhang, Li, & Shen, ) and R. padi (X. F. Sun & Li, ). Moreover, we cloned all isoprenyl diphosphate synthases in the terpenoid backbone biosynthesis pathway of A. gossypii , including FPPS, geranylgeranyl diphosphate synthase (GGPPS) and decaprenyl diphosphate synthase (DPPS; H. Zhang & Li, , ).…”
Section: Introductionmentioning
confidence: 99%